Futureristic water heater / Muhammad Yazwan Aiman Yaacob - Yaacob, Muhammad Yazwan Aiman (2021)
This case study looks at how a business went about designing, manufacturing, and marketing its goods. The chosen product for this case study was LG Inverter Heat Pump Water Heater which was a newly launched model by LG Electronics earlier December 2020. Using SWOT Analysis, we can identify the strength, weaknesses, opportunity and threats upon this product. This particular product has caught my interest as it is the first water heater model ever produced by LG. Furthermore, its features are futuristic and innovative as it can be controlled by our mobile phone through the LG ThinQ™ app, never mind from inside or outside of the home. Despite the excellent features that it has, we must take into account the marketing strategy of LG in an attempt to make the product well-known and gain as much revenue as they targeted. Hence, this case study discussed just that and offers some viewpoints to overcome challenges faced by LG.